Steel fiber reinforced concrete and preparation method thereof

By adopting steel fiber concrete and its preparation method, the shortcomings of existing concrete in terms of mechanical properties, freezing resistance and durability are solved, and higher permeability and freezing resistance are achieved, which extends the service life of concrete and ensures its quality and quality.

CN119707403APending Publication Date: 2025-03-28ZHEJIANG LONGYOU TONGQU BUILDING MATERIALS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411925599.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing low-shrinkage stable concrete has shortcomings in terms of mechanical properties, freezing resistance and durability, which affects its quality and service life.

Method used

Steel fiber concrete and its preparation method are used to prepare by mixing and mixing the raw materials combinations of specific ratios, including steel fibers, coagulant, antifreeze, etc., to improve the mechanical properties, permeability and freeze resistance of concrete.

Benefits of technology

It significantly improves the mechanical properties and durability of concrete, enhances the anti-seepage and freezing properties, thereby extending the service life of concrete and ensuring its quality and quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005209176800000091
    Figure BDA0005209176800000091
Patent Text Reader

Abstract

The invention relates to the technical field of building materials, in particular to steel fiber reinforced concrete and a preparation method thereof. The steel fiber reinforced concrete is prepared from the following raw materials in parts by weight: 900 to 1100 parts of coarse aggregate, 750 to 850 parts of fine aggregate, 360 to 400 parts of cement, 55 to 65 parts of fly ash microbeads, 25 to 35 parts of glass microbeads, 10 to 20 parts of nano titanium dioxide, 20 to 30 parts of expanding agent, 15 to 25 parts of steel fiber, 2 to 5 parts of water reducing agent, 5 to 8 parts of coagulant, 3 to 6 parts of antifreezing agent and 180 to 220 parts of water. The expanding agent is formed by compounding an SY-K type expanding fiber anti-crack waterproof agent, a CAL fiber composite quaternary expanding agent and an S-AC type high-performance concrete expanding agent according to the weight ratio of 1: (1.2-1.5): (0.8-1.2); the prepared steel fiber reinforced concrete not only has excellent mechanical properties and durability, but also has good impermeability and frost resistance, and the quality of the steel fiber reinforced concrete is effectively guaranteed while the service life of the steel fiber reinforced concrete is prolonged to a certain extent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, in particular to steel fiber concrete and a preparation method thereof. Background Art

[0002] Concrete refers to a mixture of binder (organic, inorganic or organic-inorganic composite), granular aggregate, water, and chemical admixtures and mineral admixtures that need to be added in appropriate proportions, or a composite material with a stacking structure formed after hardening. Concrete can be classified into structural concrete, mass concrete, waterproof concrete, heat-resistant concrete, expansive concrete, radiation-proof concrete, road concrete, etc. according to its use. Concrete has the characteristics of abundant raw materials, low price and simple production process, so its usage is increasing. At the same time, concrete also has the characteristics of high compressive strength, good durability and a wide range of strength grades. These characteristics make it widely used. It is not only used in various civil engineering projects, but also in shipbuilding, machinery industry, marine development, geothermal engineering and other fields. Concrete is also an important material.

[0003] A low-shrinkage stable concrete and a preparation method thereof are disclosed in the patent document with application number "CN202211595675.6". The low-shrinkage stable concrete is obtained by curing the concrete mixture into a mold, and the concrete mixture includes the following components in parts by weight: 304-320 parts of silicate cement, 76-80 parts of fly ash, 1000-1060 parts of coarse aggregate, 700-760 parts of fine aggregate, 170-180 parts of mixing water, 80-90 parts of internal curing expansion particles, and 3.8-4.0 parts of polycarboxylic acid water reducer. The concrete prepared in this patent document has excellent low shrinkage stability. However, its own mechanical properties, frost resistance and durability are relatively insufficient, which affects its quality and service life to a certain extent. Therefore, the present invention provides a steel fiber concrete and a preparation method thereof, aiming to solve the above-mentioned technical problems! Summary of the invention

[0004] The purpose of the present invention is to provide a steel fiber concrete and a preparation method thereof. The prepared concrete not only has excellent mechanical properties and durability, but also has good anti-seepage and anti-freezing properties, which prolongs its service life to a certain extent while also effectively ensuring its quality.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] A steel fiber concrete is composed of the following raw materials in parts by weight: 900-1100 parts of coarse aggregate, 750-850 parts of fine aggregate, 360-400 parts of cement, 55-65 parts of fly ash microspheres, 25-35 parts of glass microspheres, 10-20 parts of nano titanium dioxide, 20-30 parts of expansion agent, 15-25 parts of steel fiber, 2-5 parts of water reducer, 5-8 parts of coagulant, 3-6 parts of antifreeze agent and 180-220 parts of water.

[0007] Furthermore, the fine aggregate is compounded by medium sand and coarse sand in a weight ratio of 2 to 2.5:1; and the coarse sand fineness modulus is 3.2 to 3.4, and the medium sand fineness modulus is 2.5 to 3.0.

[0008] Furthermore, the coarse aggregate is compounded by fine crushed stone and coarse crushed stone in a weight ratio of 1.8 to 2.3:1; and the particle size of the fine crushed stone is 5 to 8 mm continuously assembled, and the particle size of the coarse crushed stone is 12 to 18 mm continuously assembled.

[0009] Furthermore, the water reducer is selected from any one of HTJS-5 polycarboxylate water reducer, PC-1022 polyether polycarboxylate water reducer, and sodium lignin sulfonate.

[0010] Furthermore, the expansion agent is compounded by SY-K expansion fiber anti-cracking waterproof agent, CAL fiber composite quaternary expansion agent and S-AC high-performance concrete expansion agent in a weight ratio of 1:1.2-1.5:0.8-1.2.

[0011] Furthermore, the cement model is any one of P.O42.5, P.Ⅱ42.5, PSA42.5, and PSB42.5.

[0012] Furthermore, the steel fiber has a tensile strength of ≥2500 MPa, a length of 12 to 16 mm, and a diameter of 0.18 to 0.22 mm.

[0013] Furthermore, the preparation method of the coagulant comprises the following steps:

[0014] The first step is to add methoxy PEG acrylate with a relative molecular mass of 1500 g / mol into deionized water at a dosage ratio of 0.6 to 1.0 mol / L, and then add 4-cyano-4-(thiobenzoyl) valeric acid and 0.5 to 0.8% 2,2'-azobis(2-methylpropylimidamide) dihydrochloride in molar amounts of 3 to 6% of methoxy PEG acrylate, mix and stir evenly, then heat to 65 to 75° C., and then keep warm for reaction for 6 to 12 hours under nitrogen protection;

[0015] The second step is to remove the unreacted monomers and small molecules in the product components by dialysis after the reaction is completed; then, sodium p-styrene sulfonate with a molar amount of 30-40% of methoxy PEG acrylate and methacrylic acid with a molar amount of 2-4 times that of sodium p-styrene sulfonate are added to the obtained mixed components, and the mixture is stirred evenly, and the temperature is adjusted to 60-70° C., and the mixture is kept warm for 8-15 hours under nitrogen protection; after the reaction is completed, the obtained mixture is the finished coagulant.

[0016] Furthermore, the antifreeze agent is any one of sodium nitrite, ethylene glycol and calcium nitrite.

[0017] A method for preparing steel fiber concrete comprises the following steps: accurately weighing various raw materials required for preparing the steel fiber concrete, then adding coarse aggregate, fine aggregate and cement into a mixing device, mixing and stirring at a rate of 100 to 150 r / min for 5 to 10 minutes; after the mixing is completed, adding the remaining raw materials into the mixing device, mixing and stirring evenly, and the obtained mixed slurry is the finished steel fiber concrete product.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] The present invention uses methoxy PEG acrylate, 4-cyano-4-(thiobenzoyl) valeric acid and 2,2'-azobis(2-methylpropylimidamide) dihydrochloride as raw materials, mixes and stirs evenly, and then performs heat preservation reaction under nitrogen protection, so that methoxy PEG acrylate and 4-cyano-4-(thiobenzoyl) valeric acid undergo polymerization reaction under the action of 2,2'-azobis(2-methylpropylimidamide) dihydrochloride to obtain a macromolecular reaction product. After the reaction is completed, sodium p-styrene sulfonate and methacrylic acid are added to the obtained macromolecular reaction product in sequence, and the polymerization reaction continues to occur under the protection of nitrogen after mixing and stirring evenly, and finally a coagulant finished product is prepared. The prepared coagulant can not only effectively improve the strength and durability of concrete, reduce the shrinkage rate of concrete, and reduce the probability of cracking in the later stage. It can also effectively improve the impermeability and freeze-thaw resistance of concrete and extend the service life of concrete. In the present invention, the steel fiber and the coagulant cooperate with each other, and the mutual cooperation can effectively improve the mechanical strength of concrete. The cooperation between antifreeze agent and coagulant can further improve the antifreeze performance of concrete and effectively ensure the quality of concrete.

[0020] In summary, the concrete prepared by the present invention not only has excellent mechanical properties and durability, but also has good anti-permeability and anti-freezing properties, which prolongs its service life to a certain extent while also effectively ensuring its quality. DETAILED DESCRIPTION

[0021] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0022] Example 1

[0023] A steel fiber concrete is composed of the following raw materials in parts by weight: 900 parts of coarse aggregate, 750 parts of fine aggregate, 360 parts of P.O42.5 cement, 55 parts of fly ash microspheres, 25 parts of glass microspheres, 10 parts of nano titanium dioxide, 20 parts of expansion agent, 15 parts of steel fiber, 2 parts of HTJS-5 polycarboxylate water reducer, 5 parts of accelerator, 3 parts of sodium nitrite and 180 parts of water;

[0024] Among them, the fine aggregate is compounded by medium sand and coarse sand in a weight ratio of 2:1; the coarse sand fineness modulus is 3.2, and the medium sand fineness modulus is 2.5; the coarse aggregate is compounded by fine crushed stone and coarse crushed stone in a weight ratio of 1.8:1; the particle size of the fine crushed stone is 5mm continuously assembled, and the particle size of the coarse crushed stone is 12mm continuously assembled; the expansive agent is compounded by SY-K type expansive fiber anti-cracking waterproofing agent, CAL fiber composite quaternary expansive agent and S-AC type high-performance concrete expansive agent in a weight ratio of 1:1.2:0.8; the steel fiber has a tensile strength of 2500MPa, a length of 12mm and a diameter of 0.18mm.

[0025] The preparation method of the coagulant comprises the following steps:

[0026] The first step is to add methoxy PEG acrylate with a relative molecular mass of 1500 g / mol into deionized water at a dosage ratio of 0.6 mol / L, and then add 4-cyano-4-(thiobenzoyl) valeric acid and 0.5% 2,2'-azobis(2-methylpropylimidamide) dihydrochloride in molar amounts of 3% of methoxy PEG acrylate in sequence, mix and stir evenly, heat to 65°C, and then keep the temperature under nitrogen protection for 6 hours;

[0027] The second step is to remove the unreacted monomers and small molecules in the product components by dialysis after the reaction is completed; then, sodium p-styrene sulfonate with a molar weight of 30% of methoxy PEG acrylate and methacrylic acid with a molar weight twice that of sodium p-styrene sulfonate are added to the obtained mixed components, respectively, and the mixture is stirred evenly, and the temperature is adjusted to 60°C, and the mixture is kept warm for 8 hours under nitrogen protection; after the reaction is completed, the obtained mixture is the finished coagulant.

[0028] A method for preparing steel fiber concrete comprises the following steps: accurately weighing various raw materials required for preparing the steel fiber concrete, then adding coarse aggregate, fine aggregate and cement into a mixing device, and mixing and stirring at a rate of 100 r / min for 5 minutes; after the mixing is completed, adding the remaining raw materials into the mixing device, and mixing and stirring evenly to obtain a mixed slurry that is a finished steel fiber concrete product.

[0029] Example 2

[0030] The preparation method of a steel fiber concrete provided in this embodiment is basically the same as that in embodiment 1, except that the specific composition of the steel fiber concrete and the preparation method of the coagulant are not completely the same. The specific composition of the steel fiber concrete and the preparation method of the coagulant in this embodiment are as follows:

[0031] A steel fiber concrete is composed of the following raw materials in parts by weight: 1000 parts of coarse aggregate, 800 parts of fine aggregate, 380 parts of cement, 60 parts of fly ash microspheres, 30 parts of glass microspheres, 15 parts of nano titanium dioxide, 25 parts of expansion agent, 20 parts of steel fiber, 3 parts of PC-1022 polyether polycarboxylic acid water reducer, 6 parts of accelerator, 5 parts of ethylene glycol and 200 parts of water;

[0032] Among them, the fine aggregate is made of medium sand and coarse sand in a weight ratio of 2:1; the coarse sand fineness modulus is 3.2, and the medium sand fineness modulus is 3.0. The coarse aggregate is made of fine crushed stone and coarse crushed stone in a weight ratio of 2.0:1; the particle size of fine crushed stone is 6mm continuously assembled, and the particle size of coarse crushed stone is 15mm continuously assembled; the expansion agent is made of SY-K type expansion fiber anti-cracking waterproofing agent, CAL fiber composite quaternary expansion agent and S-AC type high-performance concrete expansion agent in a weight ratio of 1:1.2:1; the tensile strength of steel fiber is 2500MPa, the length is 14mm, and the diameter is 0.2mm.

[0033] The preparation method of the coagulant comprises the following steps:

[0034] The first step is to add methoxy PEG acrylate with a relative molecular mass of 1500 g / mol into deionized water at a dosage ratio of 0.8 mol / L, and then add 4-cyano-4-(thiobenzoyl) valeric acid and 0.5-0.8% 2,2'-azobis(2-methylpropylimidazole) dihydrochloride in molar amounts of 5% of methoxy PEG acrylate, respectively, mix and stir evenly, heat to 70°C, and then keep the temperature under nitrogen protection for 10 hours;

[0035] The second step is to remove the unreacted monomers and small molecules in the product components by dialysis after the reaction is completed; then, sodium p-styrene sulfonate with a molar weight of 35% of methoxy PEG acrylate and methacrylic acid with a molar weight of 3 times that of sodium p-styrene sulfonate are added to the obtained mixed components, and the mixture is stirred evenly, and the temperature is adjusted to 65°C, and the mixture is kept warm for 12 hours under nitrogen protection; after the reaction is completed, the obtained mixture is the finished coagulant.

[0036] Example 3

[0037] The preparation method of a steel fiber concrete provided in this embodiment is basically the same as that in embodiment 1, except that the specific composition of the steel fiber concrete and the preparation method of the coagulant are not completely the same. The specific composition of the steel fiber concrete and the preparation method of the coagulant in this embodiment are as follows:

[0038] A steel fiber concrete is composed of the following raw materials in parts by weight: 1100 parts of coarse aggregate, 850 parts of fine aggregate, 400 parts of cement, 65 parts of fly ash microspheres, 35 parts of glass microspheres, 20 parts of nano titanium dioxide, 30 parts of expansion agent, 25 parts of steel fiber, 5 parts of HTJS-5 polycarboxylate water reducer, 8 parts of accelerator, 6 parts of calcium nitrite and 220 parts of water;

[0039] Among them, the fine aggregate is compounded by medium sand and coarse sand in a weight ratio of 2.5:1; the coarse sand fineness modulus is 3.4, and the medium sand fineness modulus is 3.0; the coarse aggregate is compounded by fine crushed stone and coarse crushed stone in a weight ratio of 2.3:1; the particle size of the fine crushed stone is 8mm continuously assembled, and the particle size of the coarse crushed stone is 18mm continuously assembled; the expansive agent is compounded by SY-K type expansive fiber anti-cracking waterproofing agent, CAL fiber composite quaternary expansive agent and S-AC type high-performance concrete expansive agent in a weight ratio of 1:1.5:1.2; the tensile strength of the steel fiber is 2500MPa, the length is 16mm, and the diameter is 0.22mm.

[0040] The preparation method of the coagulant comprises the following steps:

[0041] The first step is to add methoxy PEG acrylate with a relative molecular mass of 1500 g / mol into deionized water at a dosage ratio of 1.0 mol / L, and then add 4-cyano-4-(thiobenzoyl) valeric acid and 0.8% 2,2'-azobis(2-methylpropylimidazole) dihydrochloride in molar amounts of 6% of methoxy PEG acrylate, respectively, mix and stir evenly, heat to 75°C, and then keep warm for reaction for 12 hours under nitrogen protection;

[0042] The second step is to remove the unreacted monomers and small molecules in the product components by dialysis after the reaction is completed; then, sodium p-styrene sulfonate with a molar weight of 40% of methoxy PEG acrylate and methacrylic acid with a molar weight of 4 times that of sodium p-styrene sulfonate are added to the obtained mixed components, respectively, and the mixture is stirred evenly, and the temperature is adjusted to 70°C, and the mixture is kept warm for 15 hours under nitrogen protection; after the reaction is completed, the obtained mixture is the finished coagulant.

[0043] Performance test: The steel fiber concrete prepared in Examples 1 to 3 was poured into a concrete mold (size: 10 cm×10 cm×10 cm), compacted on a vibration table for 60 seconds, and then covered and cured for 28 days. Then, the following performance tests were performed on each group of steel fiber concrete samples:

[0044] 1. Compressive strength and flexural strength test: The compressive strength and flexural strength tests of each group of concrete samples were carried out in accordance with GB / T 50081-2019 "Standard for Test Methods for Mechanical Properties of Ordinary Concrete".

[0045] 2. Water penetration resistance test: Carry out water penetration resistance test on each group of concrete samples in accordance with GB / T50082-2009 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete".

[0046] 3. Freeze-thaw resistance test: The freeze-thaw resistance test of each group of concrete samples was carried out in accordance with ASTM / C "Standard Test Method for Rapid Freeze-Thaw Resistance of Concrete".

[0047] The relevant data obtained from the above tests are recorded in the following table:

[0048]

[0049] By comparing and analyzing the relevant data in the table, it can be seen that the concrete prepared by the present invention not only has excellent mechanical properties and durability, but also has good anti-permeability and anti-freezing properties, which prolongs its service life to a certain extent and also effectively guarantees its quality. This shows that the steel fiber concrete and the preparation method thereof provided by the present invention have a broader market prospect and are more suitable for promotion.

[0050] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0051] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A steel fiber concrete, characterized in that: The invention is composed of the following raw materials in parts by weight: 900-1100 parts of coarse aggregate, 750-850 parts of fine aggregate, 360-400 parts of cement, 55-65 parts of fly ash microspheres, 25-35 parts of glass microspheres, 10-20 parts of nano titanium dioxide, 20-30 parts of expansion agent, 15-25 parts of steel fiber, 2-5 parts of water reducer, 5-8 parts of accelerator, 3-6 parts of antifreeze agent and 180-220 parts of water.

2. The steel fiber concrete according to claim 1, characterized in that: The fine aggregate is compounded by medium sand and coarse sand in a weight ratio of 2 to 2.5:1; the coarse sand has a fineness modulus of 3.2 to 3.4, and the medium sand has a fineness modulus of 2.5 to 3.

0.

3. The steel fiber concrete according to claim 1, characterized in that: The coarse aggregate is compounded by fine crushed stone and coarse crushed stone in a weight ratio of 1.8 to 2.3:1; and the particle size of the fine crushed stone is 5 to 8 mm and is continuously assembled, and the particle size of the coarse crushed stone is 12 to 18 mm and is continuously assembled.

4. The steel fiber concrete according to claim 1, characterized in that: The water reducer is selected from any one of HTJS-5 polycarboxylate water reducer, PC-1022 polyether polycarboxylate water reducer and sodium lignin sulfonate.

5. The steel fiber concrete according to claim 1, characterized in that: The expansion agent is compounded by SY-K expansion fiber anti-cracking waterproof agent, CAL fiber composite quaternary expansion agent and S-AC high-performance concrete expansion agent in a weight ratio of 1:1.2-1.5:0.8-1.

2.

6. The steel fiber concrete according to claim 1, characterized in that: The cement model is any one of P.O42.5, P.Ⅱ42.5, PSA42.5, and PSB42.

5.

7. The steel fiber concrete according to claim 1, characterized in that: The steel fiber has a tensile strength of ≥2500 MPa, a length of 12 to 16 mm, and a diameter of 0.18 to 0.22 mm.

8. The steel fiber concrete according to claim 1, characterized in that: The preparation method of the coagulant comprises the following steps: The first step is to add methoxy PEG acrylate with a relative molecular mass of 1500 g / mol into deionized water at a dosage ratio of 0.6 to 1.0 mol / L, and then add 4-cyano-4-(thiobenzoyl) valeric acid and 0.5 to 0.8% 2,2'-azobis(2-methylpropylimidamide) dihydrochloride in molar amounts of 3 to 6% of methoxy PEG acrylate, mix and stir evenly, then heat to 65 to 75° C., and then keep warm for reaction for 6 to 12 hours under nitrogen protection; The second step is to remove the unreacted monomers and small molecules in the product components by dialysis after the reaction is completed; then, sodium p-styrene sulfonate with a molar amount of 30-40% of methoxy PEG acrylate and methacrylic acid with a molar amount of 2-4 times that of sodium p-styrene sulfonate are added to the obtained mixed components, and the mixture is stirred evenly, and the temperature is adjusted to 60-70° C., and the mixture is kept warm for 8-15 hours under nitrogen protection; after the reaction is completed, the obtained mixture is the finished coagulant.

9. The steel fiber concrete according to claim 1, characterized in that: The antifreeze agent is selected from any one of sodium nitrite, ethylene glycol and calcium nitrite.

10. The method for preparing steel fiber concrete according to any one of claims 1 to 9, characterized in that: The method comprises the following steps: accurately weighing various raw materials required for preparing steel fiber concrete, then adding coarse aggregate, fine aggregate and cement into a mixing device, mixing and stirring at a rate of 100 to 150 r / min for 5 to 10 minutes; after the mixing is completed, adding the remaining raw materials into the mixing device, mixing and stirring evenly, and the obtained mixed slurry is the finished steel fiber concrete product.

Citation Information

Patent Citations

  • Low-shrinkage stable concrete and preparation method thereof

    CN115974473A